Manipulating Cherenkov radiation by artificial structures - Hu, Hao (Nanyang Technological University, 2020)
Since its first experimental observation by P. A. Cherenkov in 1934, Cherenkov radiation has attracted widespread attention in both the academia and the industry in the past decades. It is well-known that Cherenkov radiation arises when a charged particle moves at a velocity exceeding the velocity threshold, i.e., the phase velocity of light in the medium. The radiation direction of the moving charged particle is intimately relevant to the particle velocity. Owing to these properties, Cherenkov radiation is widely applicated in the fields of electron microscopy, medical therapy and astronomy telescope. Even with such great achievement, Cherenkov radiation still has a broad space for the development in the future. Because electromagnetic features of Cherenkov radiation are strongly dependent on the surrounding environment, replacing natural materials by artificial structures provides enormous freedoms to manipulate Cherenkov radiation and promote its applications. Photonic crystals and metamaterials are two main classes of artificial structures. Photonic crystals are periodically structured media, whose structural dimension is proportional to the wavelength of light. The periodicity of photonic crystals is electromagnetic analogue to the atomic lattice of natural crystals. This periodic dielectric contrast experienced by the propagating light produces the photonic bandgaps of photonic crystals, where the photon transmission is prohibited. Based on the Bloch-Floquet theorem, we can artificially engineer photonic bandgaps with material constituents and structural symmetries. In the end, we are able to flexibly engineer electromagnetic states of photonic crystals. Photonic crystals have demonstrated great potentials for novel applications in optical guiding, optical trapping and optical filtering. However, when the structural dimension scales down to the subwavelength regime, the artificial structures become metamaterials. Metamaterials can be treated as homogeneous media, described within Maxwell Garnett theory. Historically, the ideas of metamaterials were initially proposed by V. Veselago, aiming to realize the negative refraction. Recent years witnessed the powerful functionalities of metamaterials, besides of the negative refraction. For example, metamaterials allow us to arbitrarily control and direct the electromagnetic fields by employing the method of transformation optics. Thanks to its ability to access and manipulate the near field, metamaterials are rapidly developing in the fields including hyperlens, invisible cloak and biosensing. In this thesis, we focus on the study of Cherenkov radiation in the one-dimensional artificial structures, including one-dimensional photonic crystals and one-dimensional metamaterials. The methods and conclusions can be extended to the two-dimensional or three-dimensional artificial structures. Below we present our three main projects on manipulating Cherenkov radiation by artificial structures. For conventional Cherenkov detectors such as the ring-imaging Cherenkov detector, the detectable momenta of charged particles are restricted by finite refractive indices of natural transparent materials. In the first work, we proposed the Brewster Cherenkov detector, which enables us to identify charged particles in a wider range of momenta than ever reported. We firstly designed a Brewster photonic crystal based on one-dimensional photonic crystals. Making the use of photonic bandgaps and the Brewster effect, the Brewster photonic crystal shows wide controllability of the dispersion-less effective refractive index. Then we studied the interplay between the charged particle and the Brewster photonic crystal. By controlling the effective refractive index of the Brewster photonic crystal, we can manipulate the Cherenkov angle at the arbitrary momentum. Homogeneous hyperbolic metamaterials are generally believed to eliminate the threshold velocity of Cherenkov radiation. Thus, Cherenkov radiation in hyperbolic metamaterials forms an important basis of threshold-free free-electron sources. However, electromagnetic features of Cherenkov radiation in hyperbolic materials with nonlocal corrections still remain elusive. In our second work, we explore the nonlocal regime of Cherenkov radiation in the hyperbolic metamaterial constructed by a periodic metallodielectric structure. We found that the spatial dispersion from the finite structural size and nonlocal electron screening in metals give rise to the Cherenkov threshold. The value of the threshold velocity is dependent on both the structural dimensions and the Fermi velocities of metals. Even though the nonlocal effects deteriorate the performance of Cherenkov sources in small-energy regimes, the additional longitudinal modes arising from the spatial nonlocality can modify and enhance the photon emission at epsilon-near-zero frequencies. Our results provide new insights to guide future experiments in low-threshold free-electron sources. Because refractive indices of natural transparent materials are finitely large, generally Cherenkov detectors are able to identify charged particles only in several gigaelectronvolt range. It still lacks an efficient way to identify charged particles in small-energy regimes. In the third work, we proposed a new type of Cherenkov detector based on longitudinal modes arising from the spatial nonlocality. We theoretically predicted that the moving charged particle on the metallic grating can produce strong longitudinal modes induced by the nonlocal electron screening in metals, only when the structural dimension is comparable to the atomistic length. Our results indicate that longitudinal Cherenkov photons has very small threshold velocity. Meanwhile, the radiation angle of longitudinal modes shows extremely high sensitivity to the particle velocity especially in small-energy regimes. This work extends the working regime of previous Cherenkov detectors below 1 GeV/c with enhanced sensitivities. In all, our work not only enriches the theory of Cherenkov radiation in the artificial structures, but also improves the performance of photonic devices based on Cherenkov radiation, including Cherenkov detectors and Cherenkov sources. In addition, our work provides a theoretical guidance for the experimental study of Cherenkov radiation in artificial structures in the future.